Optimization of Operational Management in The Automotive Spare Parts Industry - Kalyubi, Muhammad; Rozani, Neneng; Novita (Journal of Multi-Disciplines Science, 2025)
The automotive spare parts business is a promising opportunity as vehicles on the road increase. However, the success of this business is highly dependent on implementing the right management aspects to achieve short and long-term goals. Running a business opportunity is not enough with just an idea, but requires seriousness in management. This study aims to identify important aspects in the operational management of the automotive spare parts business. Using qualitative methods through interviews and document analysis, this study provides an overview of the managerial aspects that need to be applied in the management of automotive workshops. The study's results indicate that several main elements in operational management include: work schedule and capacity planning, spare parts inventory management, workforce management, and quality and service standards. These four interrelated aspects are important in smooth operations and increasing business competitiveness. These findings are expected to be a reference for business actors in managing the automotive spare parts business more effectively and efficiently.